2005
DOI: 10.17221/3394-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates: toxicology and food safety - a review

Abstract: Phthalates are organic substances used mainly as plasticisers in the manufacture of plastics. They are ubiquitous in the environment. Although tests in rodents have demonstrated numerous negative effects of phthalates, it is still unclear whether the exposure to phthalates may also damage human health. This paper describes phthalate toxicity and toxicokinetics, explains the mechanisms of phthalate action, and outlines the issues relating to the presence of phthalates in foods.  

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…However, it has been reported that cooking can eliminate most of the PAEs in vegetables (Mikula et al 2005). Therefore, reference values were calculated by the adding a removal efficiency of 80 % of the measured concentration (Mikula et al 2005).…”
Section: Target Pae Compounds In Vegetable Samples Of Four Target Invmentioning
confidence: 99%
“…However, it has been reported that cooking can eliminate most of the PAEs in vegetables (Mikula et al 2005). Therefore, reference values were calculated by the adding a removal efficiency of 80 % of the measured concentration (Mikula et al 2005).…”
Section: Target Pae Compounds In Vegetable Samples Of Four Target Invmentioning
confidence: 99%
“…Although the HQ of DEHP was estimated to be over 1, it has been reported that about 90 % of pollutants such as DEHP in foods can be hydrolyzed by enzymes from the intestines and pancreas and the remaining 10 % can be lost during the process of cooking (Mikula et al 2005) and this may ameliorate the risk to a more controllable level. The risk of other target compounds to human health may also be controllable if they can be hydrolyzed and lost during cooking.…”
Section: Bcfs Of Target Pollutants In Vegetablesmentioning
confidence: 99%
“…They are generally colourless and odourless liquids with a low solubility in water [2]. Phthalates are used as plasticizers in many consumer products, such as household furnishings, in personal care products as vehicles for fragrance, in medical devices and children's toys, in food packaging, cleaning materials or insecticides.…”
Section: Introductionmentioning
confidence: 99%